A new type of La(Fe, Si)13-based magnetocaloric composite with amorphous metallic matrix. (15th January 2015) - Krautz, Maria; Funk, Alexander; Skokov, Konstantin P.; Gottschall, Tino; Eckert, Jürgen; Gutfleisch, Oliver; Waske, Anja
Abstract : We report on novel magnetocaloric composites based on La(Fe, Si)13 particles in an amorphous metallic matrix. Hot compaction at the glass transition temperature, T g, of the matrix prevents crack formation as commonly occurs in conventional hot-compacted La(Fe, Si)13 material. This damage can affect the magnetocaloric performance. The approach in the present paper shows that the La(Fe, Si)13 particles stay intact due to the buffer-effect of the amorphous and ductile matrix at T g . Therefore, the magnetocaloric properties of the composites are almost independent of the compaction pressures.